Day-ahead Multi-objective Coordinated Optimization Strategy for Regional Scale Source Network Load Storage System. Issue 1 (March 2021) - Luo, S Q; Ding, X H; Han, T
Abstract: The regional scale source network load storage coordination system is an effective organization form to increase the proportion of clean energy and absorb distributed renewable energy. However, due to the different ownerships of various distributed resources in the system, balancing the interests of different stakeholders in the operation is an important issue to be considered. The types of distributed resources contained in the regional scale source network load and storage system and their belongingness are analyzed in different perspectives, and then the optimal operation strategy of distributed resources is proposed to balance the interests of different stakeholders. Based on this strategy, a bi-layer optimization model with energy supply cost minimization and the power consumption satisfaction maximization is established. It takes the power supply of the energy supplier and the power demand of consumer as the correlation variable of the upper and lower layer models, the analytical target cascading (ATC) theory is used to adjust the correlation variables iteratively until the power supply meets the power demand, and obtains the distributed resources trade-off operation plan satisfying different objectives. YALMIP modeling tool is used to call CPLEX solver on MATLAB platform to solve the model in parallel. An example based on the data of a regional scale source network load storage system shows that the optimization model and its solution strategy can effectively balance the optimization objectives of different stakeholders.